Reports of violence against women in different life cycles - Maísa Tavares de Souza Leite; Maria Fernanda Santos Figueiredo; Orlene Veloso Dias; Maria Aparecida Vieira; Luís Paulo Souza e Souza; Danilo Cangussu Mendes (Universidade de São Paulo, 2014)
OBJECTIVE: to analyze the reports and factors associated with violence against women. METHOD: this was a cross-sectional, exploratory and analytical study with information about the cases of reported violence, extracted from the Civil Police Report Bulletin, in a mid-sized city in Minas Gerais, Brazil. RESULTS: out of the 7,487 reports of violence against women, it was found that 44.6% of the cases were threats, 28.5% aggression, 25.1% bodily injury, 1.1% rape, and 0.7% some other type of injury. In the bivariate analysis, a higher number of cases (p=0.000) committed by partners was evidenced, for all kinds of violence except for rape. Children, adolescents and adults experienced violence by partners, followed by family members. Regarding older women, violence was committed by family members. CONCLUSION: there is the need for programs to be established to prevent violence against women in various sectors of society, permeating the life cycle.